Implementation of Agricultural Land Lease with Harvest Season Payment System in Namu Terasi Village, Sei Bingei Subdistrict, Langkat Regency - Syaufi Ginting, Muhammad Ramanda Alif; Tarigan, Tetty Marlina (IHSA Institute, 2024)
Agricultural land lease agreements with a harvest season payment system are a custom practiced by farmers in Namu Terasi Village, Sei Bingei Subdistrict, Langkat Regency. The residents of this village primarily work as farmers to sustain their livelihoods, although not all possess extensive land. Consequently, farmers in Namu Terasi Village engage in agricultural land leases with a harvest season payment system. However, some tenants fail to pay the rent within the agreed time frame, often avoiding the landowner's attempts to collect payment. In extreme cases, tenants have left the area with no known whereabouts, thus resulting in a breach of contract. This research, categorized as field research or empirical legal research, is based on primary and secondary data sources. Findings indicate that leasing agricultural land with the harvest season payment model has become customary among farmers in Namu Terasi Village, particularly for irrigated lands primarily used for rice cultivation. Lease agreements are typically conducted orally due to family connections and shared community ties. This payment system, structured around the harvest season, offers convenience to the tenant. While this lease arrangement aligns with the Civil Code’s legal contract requirements, the harvest-based payment method falls outside its purview, relying instead on mutual agreement. Should a tenant default on their obligations, they are required to compensate for any incurred costs, losses, and interest. To prevent similar issues, future lease agreements should ideally be documented in writing to ensure both parties are accountable for their respective rights and obligations